KEAMANAN WIRELESS SENSOR NETWORK PENDETEKSI KEBAKARAN HUTAN MENGGUNAKAN ALGORITMA AES PADA MEDIA KOMUNIKASI LORA - Abdul Rahman; Muhammad Sya’ban Nugroho (UPT Penerbitan Universitas Jember, 2022)
Indonesia has a vast forest area reaching 120.3 million ha in 2020. Forest fires (karhutla) in Indonesia are a problem that is often faced every year during the dry season. The development of the Wireless Sensor Network (WSN) makes it possible to place fire detection sensors in forest areas, also supported by Longe Range (LoRa) communication technology so that the range of WSN is very far. The security of data sent by sensors via WSN is essential to prevent parties from manipulating the sensor data sent. This study developed a security system for data transmitted from WSN to LoRa gateway using a 128-bit AES security system. AES is symmetric encryption, and its computational complexity is relatively tiny, so it is very suitable to be implemented in WSN. The results of this study indicate that the data read by the sensor via WSN with 128-bit AES encryption and sent to the LoRa gateway can be appropriately read using the same encryption key as the key installed on the WSN; meanwhile, if the key used is not the same, sensor data sent from WSN cannot be displayed correctly. Keywords: AES, Forest fires, Wireless Sensor Network, LoRa, Security